Development of health-promoting structures through cooperative planning Entwicklung gesundheitsförderlicher Strukturen durch kooperative Planung - Rütten, Alfred; Semrau, Jana; Wolff, Andrea R. (Pravention und Gesundheitsforderung, 2023)
Background: This article supports the theoretical foundation and specification of the concepts of “structure” and “structural change” which are fundamental to health promotion. It will enable us to design structure-related interventions in a more targeted and effective manner. In this context, cooperative planning is presented as an approach that can be used to achieve health-promoting structural change in a way that is both theory-based and practical. Materials and methods: An analysis of the scientific discourse on health-promoting structural change first reveals deficits in previous conceptualizations. Against this background, a theory-based concept of structure and a model for explaining the mechanisms of health-promoting structural change are introduced as a frame of reference. In this context, the process of cooperative planning is defined as “innovative social practice”. It will be located in the model and explained using empirical examples. Results: Necessary conditions of structural development through cooperative planning are shown. Measures developed in the cooperative process refer to health-promoting offers and infrastructure as well as to changes in political policy. Effects are illustrated in particular by changes in the capabilities of participating actors, as well as by changes in action patterns and resource allocation in the municipal context. Conclusion: Cooperative planning should be tested and further developed in the future on a broader basis and also in new fields of application.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Health promotion; Participation; Structural change; Sustainability; Theory development